"Judea Declares War on Britain": The Impact of American Jewish Anti-Nazi Protests on the Struggle for a Jewish State, 1945–1948. Issue 1 (18th March 2023) - Norwood, Stephen H
Abstract: American Jews' mass protests against Nazi antisemitism, begun soon after Hitler assumed power, provided a major impetus to, and model for, the post–World War II drive to establish a Jewish state. This postwar agitation had a considerable impact because, after the Holocaust, the Jewish population in the United States far exceeded that of any other country. The mass demonstrations of 1945–1948 were as large as those of the 1930s, even reaching 250, 000, and in both periods, it was working- and lower–middle-class Jews who provided the intense commitment and huge numbers that proved critically important. Many speakers who had addressed the anti-Nazi rallies were featured at the postwar demonstrations for a Jewish state. Now promoting Zionist goals, American Jews turned to work stoppages, neighborhood rallies, and boycotts—resuming tactics deployed in the anti-Nazi campaign. Similarly, American Jews' grassroots 1930s campaign to transport Jewish children from Nazi Germany to Palestine resurfaced after the Holocaust as a drive to generate mass support for the Haganah's efforts to run Jewish displaced persons through the British blockade of Palestine. To great effect, American Zionists also frequently drew parallels between the Nazis' actions and the British treatment of Jews in displaced persons camps, on refugee ships, and in the Yishuv.